Citronella oil-from planting to potential perspectives - Mohd Nor, Nabila Huda; Khalid, Khalisanni; Ab. Wahab, Ahmad; Bidin, Ibrahim; Othman, Maizatulnisa; Chowdhury, ZairaZaman; Ishak, Ruzaina; Khalid, Khalizani (Novus Scienta Journals, 2012)
Citronella essential oil from Cymbopogon species are widely used as flavours and fragrances in food and perfume industries, and not as insect repellent only. They also play role as antibacterial, antifungal as well as antioxidant agent based on their components like geraniol, citronellol, limonene etc. The ways to treat these plants are very important in order to get the better yield. The technique how to plant, harvest and process this tree must be considered as well as quality control in order to maintain their quality in marketing. This paper reviews about the correct technique how to plant and harvest them until the processing of citronella tree. This paper also discuss about the economic and environmental impact of citronella tree to the country.